The effect of tourism communication on the marketing of tourism services: a field study in the marshes of southern Iraq - Aayib, Ali Aoud Al-; Azeez, Zuhier Abbas (International Journal of Psychosocial Rehabilitation, 2020)
Tourism communication is one of the most powerful factors influencing the purchasing decision of the tourist, so it has become an obligation for tourism organizations to apply the concept of tourism communication in the tourism industry, as it works to provide the tourist audience with the tourism news and information needed, especially as it has become a true standard for measuring the performance of organizations Tourism and its success, in addition to that the target audience is a broad audience that needs to double efforts to ensure the delivery of the tourism message and accept it, especially in light of the intense global competition in the tourism market, so tourism organizations have become an urgent need to market their services in a way and Through its serious endeavor to provide new, varied and advanced tourism services that work to meet the needs and desires of its target tourist audience in order to maintain its market share, so this study was conducted to find out the direction that the tourism communication is taking in developing the tourism sector in general, and the extent of its impact on Marketing tourism services in the marshes of southern Iraq in particular.